A poisonous pour - Day, Maddie (Day, Maddie. Cece Barton mystery, 2026)
It's Memorial Day weekend and Sonoma County's Alexander Valley is buzzing with activity. For Cece, business at Vino y Vida is going great, as is her romance with new beau, Benjamin. Meanwhile, Cece's neighbor, Richard Flora, is stirring up controversy with his newest article, an exposé of Regan Greene, power-hungry director of a valley district organization. Also in the mix is the town's big classic car show, paired with wine tastings... At the show, Cece spots Regan, who is displaying her restored green '72 Thunderbird convertible. As Cece pours tastes, she witnesses several heated discussions with Regan -- including an argument with wine afficionado and new Colinas hardware store owner Greg Jardis. Otherwise, all goes smoothly -- until Sunday brings shocking news. Regan has been murdered... Rumors fly that Richard may have orchestrated the homicide -- or even committed it. But Cece knows that's absurd. And others in Cece's orbit seem to have discomfiting connections to Regan, from Cece's employee, Dane, to her winemaking teacher's sister, Yolanda, to Colinas Mayor Guittierez. And after Yolanda visits the wine bar, Benjamin says he recognizes her from a road race. Determined to clear Richard's name, and failing to extract any clues from detectives, Cece once again enlists her twin, Allie, as her partner-in-sleuthing. But they'll have to act quickly, before the trail goes sour... --